Effect of stir casting process parameters on tribological performance of Al6061-SiCp composite - Adebisi, A. A.; Maleque, Md. Abdul; Bello, K. A. (2016)
In this study, the tribological performance of Al6061-SiCp composite is investigated considering the influence of stir casting process parameters. The wear and frictional characteristics were studied using the dry reciprocating wear testing machine. Experimentation is generated through the central composite design (CCD) using a four factor five level design plan. The process parameters (reinforcement fraction wt%, stirring speed rpm, processing temperature °C and processing time s) are examined using ANOVA and multiple objective optimization (MOO) analysis. The result shows that stirring speed has the most significant contribution in controlling the wear and friction characteristics. Confirmation test is also conducted to verify and validate the process parameters in order to optimize the tribological output. Moreover, characterization of the composite wear scar mechanism is performed using scanning electron microscope. This study provides an effective method of minimizing the tribological properties of Al6061-SiCp composite by optimizing the stir casting process parameters.